Proses Reduksi Selektif Bijih Nikel Limonit Menggunakan Zat Aditif CaSO4 [Selective Reduction Process of Nickel Limonite With Adictive CaSO4] - Wahyu Mayangsari; Agus Budi Prasetyo (National Research and Innovation Agency (BRIN), 2016)
This research aims to determine the optimum selective reduction conditions process of limonite nickel ore using additives CaSO4 and followed by magnetic separation to improve the nickel content. The selective reduction process was carried out at temperature range of 800 – 1100 °C, 1-4 h of reduction time, and the addition of the reducing agent and additives 5% - 20%. Limonite nickel ore was prepared by heating the ore inside the oven, size reduction and sieving to get ore with size under 100 mesh. Then, limonite nickel ore was mixed with reducing agent and additive. In addition, the limonite nickel ore which was mixed with the reducing agent and additive, was reduced in muffle furnace carbolite at certain temperature and time. Reduction result was weighed and concentrated by magnetic separation process, and the result was analysedby AAS (atomic absorption spectrometry) to determine of Ni contents in concentrates. The results showed that the higher a reduction temperature, Ni content and metallization of Ni was improved with the formation of Ni metal which separated from the Fe metal. The similar result was found with longer of reduction time. On the contrary, the higher an addition of reducing agent in the reduction mixture, the Ni content decreased slightly. The addition of CaSO4 can increasing the nickle content but it was not given the tendency for the good results. The highest increasing of nickel contents i.e. 2,44% was achieved at 1100 ºC of reduction temperature, 1 h of reduction time, 10% addition of reducing agent and 20% addition of CaSO4 additive. The recommended reduction temperature are 1100 °C for 1 h of reduction time, with 10% addition of reducing agent and 20% addition of CaSO4 additive.AbstrakPenelitian ini bertujuan untuk mengetahui kondisi optimum pada proses reduksi selektif bijih nikel limonit menggunakan zat aditif CaSO4 dan diikuti dengan pemisahan magnetik untuk mendapatkan peningkatan kadar nikel. Proses reduksi selektif dilakukan pada rentang suhu 800 - 1100 °C, waktu reduksi 1 – 4 jam, serta penambahan reduktor dan aditif 5% - 20%. Preparasi bijih nikel limonit dilakukan dengan pemanasan bijih dalam oven, pengecilan ukuran dan pengayakan untuk mendapatkan bijih dengan ukuran lolos 100 mesh. Kemudian dilakukan pencampuran bijih nikel limonit dengan reduktor dan aditif. Campuran bijih nikel limonit kemudian direduksi dalam muffle furnace carbolite pada suhu dan waktu tertentu. Hasil reduksi kemudian ditimbang dan dikonsentrasikan menggunakan proses pemisahan magnetik dan hasilnya dianalisis dengan metode AAS (atomic absorption spectrometry) untuk mengetahui kadar Ni pada konsentrat. Hasil penelitian menunjukkan bahwa semakin tinggi suhu reduksi, peningkatan kadar Ni dan metalisasi logam Ni semakin tinggi, dengan terbentuknya logam Ni yang terpisah dari logam Fe. Hal yang sama juga terjadi jika waktu reduksi semakin lama. Namun, semakin banyak penambahan reduktor pada campuran reduksi, peningkatan kadar Ni semakin kecil. Penambahan CaSO4 dapat meningkatkan kadar nikel namun belum memberikan kecenderungan hasil yang baik. Peningkatan kadar Ni tertinggi yang didapatkan adalah 2,44%. Direkomendasikan untuk menggunakan suhu reduksi 1100 °C, waktu reduksi 1 jam, penambahan reduktor 10% dan penambahan aditif CaSO4 20%.